2022
DOI: 10.1002/adbi.202200006
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation: “The Master Key” to Deciphering the Physiological and Pathological Functions of Cells

Abstract: Phase separation is a hot research field at present. It involves almost all aspects of cells and plays a significant role in cells, promising to be “a master key” in unlocking the mysteries of nature. In this review, the factors that affect phase separation are introduced, such as own component, electrostatic interaction, and chemical modification. Furthermore, the physiological roles of phase separation in cells, including molecules transport channel, gene expression and regulation, cellular division and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…Until a few years ago, lncRNA was regarded as a superfluous substance transcribed by genes ( 49 ). However, some in-depth studies have proved that lncRNA was involved in the biological activities of genes ( 50 52 ). LncRNA is closely related to tumor function.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few years ago, lncRNA was regarded as a superfluous substance transcribed by genes ( 49 ). However, some in-depth studies have proved that lncRNA was involved in the biological activities of genes ( 50 52 ). LncRNA is closely related to tumor function.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00707, EMS2OS, and NR2F2-AS1 were expressed in IMvigor210 bladder cancer, where a high-risk score implies a higher survival rate, which was unexpected. Increased expression of stem cell-associated biomarkers in tumor cells is highly correlated with drug resistance, cancer recurrence, and tumor proliferation ( 71 , 72 ). In our study, the stem cell index was not significantly associated with OS between high and low expression subgroups, suggesting that the degree of cancer progression is not related to OS.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular chaperones are molecular assistants that assist in the folding and assembly of intracellular proteins and play an important role in intracellular life activities ( Shan et al, 2020 ; Wei et al, 2022 ). Studies have shown that molecular chaperones play an important role in the occurrence and development of tumors, and it has also been confirmed as a prognostic marker for tumors ( Zhu et al, 2013 ; Lu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%